Evaluación de la eficacia del ciclo básico acelerado en el proceso de reinserción escolar de las adolescentes de 11 a 17 años que han sido víctimas de trata y explotación sexual comercial - Cárdenas Del Hierro, Andrea Milena (2013)
The rates in the country cases of human trafficking in its various types are increasingly alarming, although authorities such as the Ministry of Interior, the Prosecutor, among other organizations DINAPEN put all the tools at its disposal to combat this problem. But the situation starts with the lack of family’s uptake processes of children and adolescents outside schools or colleges, you need that in Ecuador there is prevention workshops, working groups and roundtables on the topic for members of society to know all the implications of the XXI century slavery now known Trafficking in Persons, so-called White Slave Traffic.